Disiplin kerja, etos kerja dan kesempatan berprestasi dengan produktivitas kerja perawat rumah sakit - Riyanti Riyanti; Andri Yulianto (Holistik Jurnal Kesehatan, 2020)
Hospital nurses’  job performance: Discipline, ethos at work and opportunity to reach a great accomplishmentBackground: Hospitals as health care institutions must be able to provide quality and quality services in terms of good service to patients. Based on observations made by researchers from January 2 to 10 2019. Based on the results of interviews with 10 patients in the hospital found out of 10 people as many as 7 people (70%) stated that the services of health workers were not fast, of 10 people as many as 5 people stated officers arrive late when needed.Purpose: knowing corelation of a work discipline, ethos at work, and opportunities for personal achievement among hospital nurses.Method: Observational analytic research design with cross sectional method. This research was conducted in May in Zainal Abidin Pagar Alam Hospital, Way Kanan. The object of this research is work discipline, work ethic and opportunity to perform as independent variables and work productivity as the dependent variable. The subject of this research is nurses as permanent employees and contracts. Collecting data with a questionnaire. Data analysis was univariate and bivariate (chi square).Results : based on the results of the study it is known that most of the respondents with good work productivity as much as 38 (56.7%) respondents, good work discipline as many as 36 (53.7%) respondents, good achievement opportunities as many as 37 (55.2%) respondents and work ethic both 42 (62.9%) respondents. There is a relationship between work discipline and nurse work productivity (p-value = 0,000 OR 14,375). There is a relationship of opportunity for achievement with nurse work productivity (p-value = 0,000 OR 11,786). There is a relationship between work ethic and nurse work productivity (p-value = 0.004 OR 5.313).Conclusion: There was corelation of a work discipline, ethos at work, and opportunities for personal achievement among hospital nurses. Suggestions for hospitals Determination of work schedules according to the percentage of time used will likely prevent waste and work will be effective and efficient.Keywords: Hospital nurses; Job performance; Discipline; Ethos; Opportunity; AccomplishmentPendahuluan: Rumah sakit sebagai institusi pelayanan kesehatan harus mampu memberikan pelayanan yang bermutu dan berkualitas dari segi pelayanan yang baik kepada pasien. Berdasarkan hasil pengamatan yang dilakukan oleh peneliti dari tanggal 2 – 10 Januari 2019. Berdasarkan hasil wawancara dengan 10 pasien  di Rumah Sakit didapati dari 10 orang sebanyak 7 orang (70%) menyatakan pelayanan petugas kesehatan yang kurang cepat, dari 10 orang sebanyak 5 orang menyatakan petugas datang terlambat saat dibutuhkan. Tujuan: Diketahui hubungan kedisiplinan kerja, etos kerja dan kesempatan berprestasi dengan produktivias kerja perawat.Metode: Desain penelitian analitik observasional dengan metode cross sectional. Penelitian ini telah dilakukan pada bulan Mei 2019.  disiplin kerja, etos kerja dan kesempatan berprestasi sebagai variabel bebas dan produktivitas kerja sebagai variabel terikat. Subjek penelitian ini perawat sebagai karyawan tetap maupun kontrak. Pengumpulan data dengan kuesioner. Analisis data secara univariat dan bivariat (chi square).Hasil: berdasarkan hasil penelitian diketahui sebagian besar dari responden dengan produktivitas kerja baik sebanyak 38 (56,7%) responden, disiplin kerja baik sebanyak 36 (53,7%) responden, kesempatan berprestasi baik sebanyak 37 (55,2%) responden dan etos kerja baik sebanyak 42 (62,9%) responden. Ada hubungan disiplin kerja dengan produktivitas kerja perawat (p-value = 0,000 OR 14,375). Ada hubungan kesempatan berprestasi dengan produktivitas kerja perawat ( p-value = 0,000 OR 11,786). Ada hubungan etos kerja dengan produktivitas kerja perawat (p-value = 0,004 OR 5,313).Simpulan: Ada hubungan kesempatan berprestasi dengan produktivitas kerja perawat. Ada hubungan etos kerja dengan produktivitas kerja perawat. Saran bagi rumah sakit Penetapan jadwal pekerjaan menurut prosentase waktu yang digunakan kemungkinan akan mencegah terjadinya pemborosan dan pekerjaan akan menjadi efektif dan efisien.